Developing High Performance Personnel in an Institute Environment - Collins, D. (3rd International Forum on Elite Sport. Burleigh Court, Loughborough University, 9-11 September 2003, 2003)
Powerpoint-Präsentation zur Trainerausbildung an der Universität Edinburgh (Grossbritannien)